Assessment of national-level progress towards elements of the Aichi Biodiversity Targets. (September 2020) - Buchanan, Graeme M.; Butchart, Stuart H.M.; Chandler, Georgina; Gregory, Richard D.
Highlights: Independent national assessments of progress to Aichi biodiversity targets are lacking. Using developed indicators at national level describes variation in progress to elements. Insufficient progress being made on elements. Progress often correlated with governance, GDP, population density & urbanisation. Abstract: Progress towards the Aichi Targets adopted through the Convention on Biological Diversity has been measured globally via indicators linked to elements of targets (the 20 targets consist of 54 elements), and nationally based on reporting by parties to the convention in the 5th (2010–2014) and 6th (2014–2018) National Reports. Here we used selected indicators that are readily available for each country to score national level progress ('moving towards the target', 'little or no progress', or 'moving away from target') for 11 elements of eight Aichi Targets (1, 4, 5, 7, 11, 12, 19, 20). Across the selected indicators, elements, and countries for which data were available, in 24.2% of cases countries were moving towards the elements, for 22.3% they were moving away, and for 53.5% there was little or no progress. This overall level of progress is similar to progress to targets as reported in the 5th and 6th National Reports. National progress to three of the 11 elements was positively correlated with progress to targets reported in the 5th National Reports, while progress to none of the elements was correlated with progress reported in the 6th National Reports. Progress to many of the elements considered was positively correlated with better governance, and to a lesser extent GDP per capita, population density and urbanisation. We suggest that post-2020 biodiversity targets should be designed taking greater account of their measurability, and will require improved biodiversity monitoring, both of which would facilitate more effective assessment of progress and enable more insightful policy responses.